Giant electronic polarization induced by a helical spin order in SrMn7O12: First-principles calculations. (7th January 2015) - Liu, H. M.; Dong, Shuai; Du, Z. Z.; Chu, P.; Liu, J.-M.
Abstract: Through first-principles density functional calculations, the magnetic ground state and electronic structure of mixed-valent manganite SrMn7 O12 in the rhombohedral symmetry are investigated in detail. Our calculations show clearly that the possible magnetic ground state accommodates a particular helical spin order responsible for the insulating state in SrMn7 O12 . The giant ferroelectric polarization is revealed, which is almost purely from the electronic contribution rather than the ionic displacements and is closely related to the magnetism. The influence of the on-site Coulomb interaction and spin-orbit coupling on the electronic structure and multiferroicity is also discussed. The present results suggest that SrMn7 O12 is a promising multiferroic candidate with desirable properties.